2011
DOI: 10.1128/iai.05412-11
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of GAMA, a Plasmodium falciparum Merozoite Micronemal Protein, as a Novel Blood-Stage Vaccine Candidate Antigen

Abstract: One of the solutions for reducing the global mortality and morbidity due to malaria is multivalent vaccines comprising antigens of several life cycle stages of the malarial parasite. Hence, there is a need for supplementing the current set of malaria vaccine candidate antigens. Here, we aimed to characterize glycosylphosphatidylinositol (GPI)-anchored micronemal antigen (GAMA) encoded by the PF08_0008 gene in Plasmodium falciparum. Antibodies were raised against recombinant GAMA synthesized by using a wheat ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
86
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(97 citation statements)
references
References 37 publications
(55 reference statements)
10
86
1
Order By: Relevance
“…Female BALB/c mice (DaehanBiolink Co., Eumsung, ROK) were used at 5 to 7 weeks of age. Groups of three mice were injected intraperitoneally with 20 g of MSP1P-30, -42, -33, and -19, or MSP1-19, and phosphatebuffered saline (PBS) with Freund's complete adjuvant (Sigma-Aldrich, St. Louis, MO) as described previously (31). Booster injections were given 3 and 6 weeks after the priming using the same amount of antigen with Freund's incomplete adjuvant (Sigma-Aldrich), and mouse sera were collected 2 weeks after the final boost.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Female BALB/c mice (DaehanBiolink Co., Eumsung, ROK) were used at 5 to 7 weeks of age. Groups of three mice were injected intraperitoneally with 20 g of MSP1P-30, -42, -33, and -19, or MSP1-19, and phosphatebuffered saline (PBS) with Freund's complete adjuvant (Sigma-Aldrich, St. Louis, MO) as described previously (31). Booster injections were given 3 and 6 weeks after the priming using the same amount of antigen with Freund's incomplete adjuvant (Sigma-Aldrich), and mouse sera were collected 2 weeks after the final boost.…”
Section: Methodsmentioning
confidence: 99%
“…Eight fragments of DNA encoding PvMSP1P-83A, -83B, -83C, -30, -38, -42, -33, and -19 were amplified and cloned into pEU-E01-His-TEV-MCS vector (CellFree Sciences), and the cloned inserts were sequenced using an ABI 3700 genetic analyzer (Genotech, Daejeon, South Korea). Those proteins, including PvDBP region II (PvDBPII) and PvMSP1-19, were also expressed using a WGCF expression system (CellFree Sciences) and purified using Ni-affinity chromatography as described previously (31)(32)(33).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a few reports have demonstrated that targeting combinations of merozoite antigens (including EBA and PfRH) yielded potent invasion inhibition (15,19,20). However, those studies did not demonstrate invasion-inhibitory efficacy against heterologous P. falciparum clones, which exhibit different invasion phenotypes.…”
mentioning
confidence: 97%
“…The quality of protein expression and folding had been validated previously for some of the protein constructs used by demonstrating that vaccine-induced Abs raised against the recombinant protein recognize native protein (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37); vaccine-induced Abs have functional antiparasite activity in growthinhibition assays (GIAs) or Ab-dependent cellular-inhibition (ADCI) assays (12,28,30,(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43); or the recombinant protein has appropriate biological function by binding its receptor (25,28,34,35,38,39) (Supplemental Table I). Validation of WGCF as an appropriate system for expression of P. falciparum merozoite proteins has also been established in several ways.…”
Section: Expression Of Ragsmentioning
confidence: 99%